RoadRunner: a fast and flexible exoplanet transit model. Issue 2 (25th September 2020) - Parviainen, H
ABSTRACT: I present RoadRunner, a fast exoplanet transit model that can use any radially symmetric function to model stellar limb darkening (LD) while still being faster to evaluate than the analytical transit model for quadratic LD by Mandel & Agol. CPU and GPU implementations of the model are available in the pytransit transit modelling package, and come with platform-independent parallelization, supersampling, and support for modelling complex heterogeneous time series. The code is written in numba -accelerated python (and the GPU model in opencl ) without c or fortran dependencies, which allows for the LD model to be given as any python -callable function. Finally, as an example of the flexibility of the approach, the latest version of pytransit comes with a numerical limb darkening model that uses LDTk -generated limb darkening profiles directly without approximating them by analytical models.